Constitutive equation for describing true stress–strain curves over a large range of strains. (2nd October 2020) - Cao, Jun; Li, Fuguo; Ma, Weifeng; Li, Dongfeng; Wang, Ke; Ren, Junjie; Nie, Hailiang; Dang, Wei
ABSTRACT: Full-range strain hardening behaviour, containing the post-necking stage, is difficult to account for in detail. Hence, a Swift–Voce (S–V) model was used to describe the full-range stress–strain behaviour of 7050-T7451 aluminium alloy under uniaxial-tension, tension-with-notch and pure-shear processes with a hybrid experimental-numerical framework. Since the S–V model is not able to describe accurately the behaviour of Ti–6Al–4V alloy, a combined Swift and 4th degree polynomial (S-P4) model is proposed. Results indicate that the S–V model can successfully describe large-deformation behaviour of the 7050-T7451 aluminium alloy, and the S-P4 model can successfully describe that of the Ti–6Al–4V alloy based on careful designing process of the constitutive equation.